Increased Response-Time Variability Across Different Cognitive Tasks in Children With ADHD. (July 2014) - Adamo, Nicoletta; Di Martino, Adriana; Esu, Lidia; Petkova, Eva; Johnson, Katherine; Kelly, Simon; Castellanos, Francisco Xavier; Zuddas, Alessandro
Objective: Increased response-time (RT) fluctuations below 0.2 Hz have been reported as characteristic of ADHD in some but not all studies, possibly due to methodological differences. Accordingly, We contrasted two tasks and two analytical approaches in the same sample of children with ADHD.Method: Fifty-two children with ADHD and 49 typically developing children completed an Eriksen Flanker Task and a fixed-sequence version of the sustained attention to response task. RT fluctuations with two different frequency analyses were examined.Results: Robust ADHD-related increases of slow RT fluctuations within all frequencies were found in both tasks. Tasks were significantly correlated in both groups for frequencies above 0.07 Hz. RT fluctuations across all frequencies were greatest in children with ADHD with abnormally elevated omissions.Conclusion: We observed significantly increased fluctuations of RT in children with ADHD across two different tasks and methods supporting the hypothesis that slow frequency RT fluctuations reflect neurophysiological processes underlying ADHD.